KARAKTERISTIK MATAAIR KARST DI KECAMATAN TAMBAKBOYO, KABUPATEN TUBAN, JAWA TIMUR - , CHABIBUL MIFTA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was done on Lamijah Spring, Pok Bango Spring, and Belik Anget Spring in the Tambakboyo District, Tuban. The purpose of this research is : (1) to know the spatial and temporal variations of Spring debit on Lamijah Spring, Pok Bango Spring, and Belik Anget Spring